Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022 22nd IEEE International Symposium on Cluster, Cloud and Internet Computing (CCGrid) 2022
DOI: 10.1109/ccgrid54584.2022.00106
|View full text |Cite
|
Sign up to set email alerts
|

AIBLOCK: Blockchain based Lightweight Framework for Serverless Computing using AI

Abstract: Artificial intelligence (AI)-based studies have been carried out recently for the early detection of COVID-19. The goal is to prevent the spread of the disease and the number of fatal cases. In AI-based COVID-19 diagnostic studies, the integrity of the data is critical to obtain reliable results. In this paper, we propose a Blockchain-based framework called AIBLOCK, to offer the data integrity required for applications such as Industry 4.0, healthcare, and online banking. In addition, the proposed framework is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 20 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…Vehicular Edge Computing introduces a computation offloading mechanism with embedded devices in cars offloading data to MEC servers [46]. Implementing offloading and computation resource mechanisms will improve the utilization of MEC servers [48]. Client Edge Computing, including CCTV cameras, mobile phones and smart sensors, can perform some processing rather than sending all data to the edge network; therefore, this model can be helpful to service providers [49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vehicular Edge Computing introduces a computation offloading mechanism with embedded devices in cars offloading data to MEC servers [46]. Implementing offloading and computation resource mechanisms will improve the utilization of MEC servers [48]. Client Edge Computing, including CCTV cameras, mobile phones and smart sensors, can perform some processing rather than sending all data to the edge network; therefore, this model can be helpful to service providers [49].…”
Section: Discussionmentioning
confidence: 99%
“…However, this technology imposes a high risk to privacy because single user data is transferred to a central cloud for storage and processing [157]. Edge Computing eliminates the need for such long-reach data transmission if more local computational resources are available [48]. Pre-processing can be performed at the edge node in this case as with the smart parking scenario discussed above.…”
Section: Daily Activities (Mobile Health)mentioning
confidence: 99%
See 1 more Smart Citation
“…Serverless creates new containers to handle these requests; thus, new cold start latencies occur. In addition, it has been observed that the amount of CPU and RAM of the system and the software languages used to execute the function affect cold start latency [10].…”
Section: Limitations and Challengesmentioning
confidence: 99%
“…T HE proliferation of Internet of Things (IoT) applications has led to a substantial increase in the volume of data that requires processing [1]. IoT devices are inherently resource-constrained, and as such, cloud systems can address this limitation by providing the resources and processing power they offer.…”
Section: Introductionmentioning
confidence: 99%